From lessons to sessions: How does second language teaching experience translate to psychoeducational group facilitation? - Burke, Evan (Groupwork, 2017)
Abstract: Reflection on the planning and facilitation of a social work psychoeducational group led to an examination of the transferability of teaching experience. Social interaction in second language studies allows for the learning of skills and knowledge through the mediation of teachers and fellow students. Likewise, psychoeducational groups, in having educational and instructional elements, encourage members to employ learning skills in jointly constructing ideas and strategies related to strengths, emotional resilience and thinking habits. Groupworkers seek to identify and activate the strengths present in members just as teachers do with the knowledge present in students. The communicative approach to language teaching encourages student comfort with working with peers in group tasks so that the teacher becomes facilitator and this translates to psychoeducational groups in terms of mutual aid, anxiety reduction, inclusion and altruism. Group members embrace this and groupworkers benefit from challenging themselves in planning such group sessions. Keywords: social work;, teaching; psychoeducational; mental health; strengths; resilience; groupwork; group work